Patient's satisfaction with dental clinics and treatment at Riyadh Elm University - Abdulrahman Al Saffan; Rana Babsail; Yasmen Al Shilawy; Yara Alsoqair; Lamis Murshid; Rawan Alshehri; Shahad Alshehri; Lama Al Marshad (Wolters Kluwer Medknow Publications, 2019)
Background: Satisfaction of the patient plays a key role in determining the correlation between the quality of health-care services provided and the patients' trust. The objective of this study was to determine the level of satisfaction regarding the quality of dental care among patients at dental clinics of Riyadh Elm University. Materials and Methods: Self-administrated questionnaire was distributed to patients attending clinics of Riyadh Elm University. Questionnaire consisted of items on appointment availability, satisfaction with the performance of the reception, satisfied with your treating practitioner, treatment fees, satisfied with the level of cleanliness/sterilization, compassionate and caring of the support staff and treatment provider, and finally overall evaluation of the services received within the clinics. Results: A total of 600 questionnaires were collected from the electronic system used in the dental clinic of Riyadh Elm University. 89% of the participants agreed that it was easy to get an appointment in the dental clinics and 59% were very satisfied with the performance of the reception. Majority of the participants were satisfied with the treatment provider (80%), 82% were satisfied with treatment fees, 74% patients were very satisfied with the cleanliness, 81% agreed that the treating practitioner and supporting staff were compassionate and caring, and most of the participants were satisfied with services received in the dental clinic of Riyadh Elm University. Conclusions: Dental clinic of Riyadh Elm University has been successful in achieving participant's satisfaction regarding the services, staff, treatment, and fees.